General health and functional improvement among patients with unstable extracapsular proximal femoral fractures managed with proximal femoral nail by using SF-36 score - Verma, Amit Kumar; Dhiman, Priyanka; Sharma, Vipin (International Journal of Research in Orthopaedics, 2022)
Background: Proximal femoral nail is emerging as the treatment of choice for unstable extra capsular proximal femoral fractures. This study comprises of functional evaluation of the treated patients by using SF 36 score. Methods: This was a prospective hospital-based study done on 54 patients with unstable proximal femoral fractures classified according to the AO/ASIF classification system and were treated by using PFN in the department of Orthopaedics DRPGMC, Tanda. Functional outcome was assessed by using SF-36 score on, 14th postoperative day, at three months and six months. Results: Our study has mean scores of short form-36 subscales as physical function 70.6, role limitation due to physical health 68.1, role limitation due to emotional health 90, energy/fatigue 66, emotional wellbeing 78, social functioning 67.7, pain 75 and general health 73.3. Conclusions: The results of this study confirm that intramedullary nailing with the use of a PFN in unstable proximal femoral fractures is a safe method. A significant change was seen in quality of life postoperatively as evidenced by various scores used in present study. Weaknesses of this study include a short follow-up period and the inclusion of a small study group.